Cleaners' perceptions of the pending municipal merger in the west rand - Mokoena, Pinkie Lucia Jennifer (My University, 2018)
When change is introduced in the workplace, marginalized employees may develop a negative attitude towards the process due to ignorance and fear. The study aimed to explore the cleaning staffs’ perceptions on the municipal pre- mergers between two West Rand Municipalities. The focus study was to explore the cleaning staff members’ emotions and reactions towards the merger before it was to be implemented specifically focusing on their perceptions around job security, job responsibility, and communication. There is currently little research done on pre-mergers, especially between political organizations. The research followed a qualitative approach in a form of a case study. Face to face interviews were conducted with seventeen (17) cleaning staff from two Municipalities to collect data utilizing a self – developed, semi structured interview schedule. Sampling was done using a non-probability convenience sampling method. These employees are usually marginalized and have limited if any decision making powers in their working space. The data was analysed utilizing thematic analysis. The findings identified that even the most marginalized of employees could have an impact on change processes based on several factors and there is a relationship between a previous workplace change experience and a new one. The study transformed into a comparative study as marked differences emerged because one of the Municipalities had been through a merger previously and it had a different impact as compared to those who had not gone through the merger process previously. The findings revealed that communication strategies impact on the perceptions of all levels of employees regardless if they participate in the planning process of any organisational change process or not. Open communication and constant consultation by an employer was found to inspire employees to do well because they become confident of their future within the organization. The research findings carve a way to future pre- merger studies with deeper insight into the usually marginalized groups in the workplace.
A report on a research study presented to The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfillment of the requirements for the degree Master of Arts in Social Work January 2018
Keywords: Consolidation and merger of corporations; Organizational change--Management